2021
DOI: 10.1177/1359105321999090
|View full text |Cite
|
Sign up to set email alerts
|

Worry much? Preventive health behaviours related to worry across countries amid COVID-19

Abstract: This study examined the relationship between worry and health behaviours using an online survey of 69,033 respondents from 32 countries. We hypothesized that past health behaviours predicted worry experienced, which in turn predicted future health behaviours, and included a metric of cultural distance from the US. Past behaviours such as maintaining physical distance predicted higher worry, whereas worry reduced the likelihood of going outside. Being culturally dissimilar to the US was associated with lower wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…avoiding crowds, mask wearing, quarantining) which have taken place during the pandemic and sources of social support are related to parent mental health. It is possible that increased vigilance about viral contraction or transmission, tied to these behaviors, is associated with greater worry (Kapoor and Tagat, 2021), fear (Giordani et al, 2020), and anxiety, especially for parents whose caregiving role involves protecting the health of their children and family members. On the other hand, it is possible that preventive health behaviors constitute a means of active coping that may be optimal for one’s mental health (Li and Xu, 2020; Nelson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…avoiding crowds, mask wearing, quarantining) which have taken place during the pandemic and sources of social support are related to parent mental health. It is possible that increased vigilance about viral contraction or transmission, tied to these behaviors, is associated with greater worry (Kapoor and Tagat, 2021), fear (Giordani et al, 2020), and anxiety, especially for parents whose caregiving role involves protecting the health of their children and family members. On the other hand, it is possible that preventive health behaviors constitute a means of active coping that may be optimal for one’s mental health (Li and Xu, 2020; Nelson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only 12 studies took an explicitly cross‐cultural perspective. The constructs under measurement included individualism versus collectivism (e.g., Tang et al, 2021), cultural distance (e.g., Kapoor & Tagat, 2021) and worldviews on nature (e.g., Haas et al, 2021). Gokmen et al (2021) found cultural differences to predict COVID‐19 severity in very highly developed European countries using measurement of six cultural dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…For measures, the exclusive reliance on self-report methods inflates shared method variance and also increases the likelihood of social desirability bias (i.e., overreporting or underreporting; Tunçgenç et al, 2021). Another concern noted was that newly developed COVID-19 scales may not yet accurately capture the complexity of COVID-19-related experiences (Götz et al, 2021), and, on a related note, that findings in this early stage of the pandemic may under-represent mental health concerns that might only emerge over a longer period of the pandemic (Kapoor et al, 2021).…”
Section: Rq5: Reported Challenges Of the Research Process During Covi...mentioning
confidence: 99%
“…A study by Dao and Lim (2022) Oceania countries account for 7% of the studies, with Australia having the maximum number of studies compared to New Zealand. However, India features in just seven studies, of which one study is from 2014 (Kapadia-Kundu et al, 2014), and the remaining six have been published only in the last 2 years (Ghosal et al, 2022;Kapoor & Singhal, 2021;Kapoor & Tagat, 2022;Raman & Aashish, 2023;Shahnawaz et al, 2023;Wang et al, 2021). Since 1998, only a few cross-country studies have been performed.…”
Section: Theory References Amentioning
confidence: 99%